2014
DOI: 10.1002/biot.201300495
|View full text |Cite
|
Sign up to set email alerts
|

Antibody approaches to prepare clinically transplantable cells from human embryonic stem cells: Identification of human embryonic stem cell surface markers by monoclonal antibodies

Abstract: Human embryonic stem cells (hESCs) are unique cell populations, possessing both unlimited self-renewal capacity and pluripotency, i.e. the potential to give rise to all kinds of specialized cells in the human body. Marker molecules expressed on the surface of hESCs are important for the identification, characterization, and clinical application of hESCs. Compared with conventional genomics- or proteomics-based approaches, generating monoclonal antibody (mAb) libraries against hESCs using alternative methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…While published genomic‐ and proteomic‐based studies have previously identified some of these candidate extracellular hPSC markers , to date the existing antibodies for these proteins, many of which are polyclonal, have not been demonstrated to effectively detect epitopes on live hPSCs. Since the mAbs reported in this study have been raised to known protein antigens and all were specifically screened for detection on live hPSCs, these mAbs provide a greatly expanded resource for a variety of applications, including purification of subpopulations, removal of unwanted cells from differentiating hPSC derivatives, and detailed study of the nature of pluripotency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While published genomic‐ and proteomic‐based studies have previously identified some of these candidate extracellular hPSC markers , to date the existing antibodies for these proteins, many of which are polyclonal, have not been demonstrated to effectively detect epitopes on live hPSCs. Since the mAbs reported in this study have been raised to known protein antigens and all were specifically screened for detection on live hPSCs, these mAbs provide a greatly expanded resource for a variety of applications, including purification of subpopulations, removal of unwanted cells from differentiating hPSC derivatives, and detailed study of the nature of pluripotency.…”
Section: Resultsmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) are especially useful because of their sensitivity and specificity. However, many of the conventionally used cell surface markers for hPSCs are not reactive with proteins, but instead recognize complex carbohydrate or lipid moieties for which there are no identified corresponding genes . Some of the markers used for characterization of hPSC lines are also immunoreactive in mature cell types, so are useful only within a limited time frame of hPSC culture .…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of cell surface markers have been reported to be indicative of undifferentiated hPSCs, including carbohydrate-associated molecules such as TRA-1-60, TRA-1-81, SSEA-3, -4, and -5 and cell adhesion molecules, and claudin-6 (Ben-David et al., 2013, Choi et al., 2014, Son et al., 2011). However, most of them are directed against carbohydrate antigens and their exact functions are not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, cell surface molecules of PSCs represent useful tools for identifying unique cell populations with self-renewal capacity and eliminating residual undifferentiated PSCs from differentiated derivatives. However, the cell surface molecules conventionally used to identify undifferentiated PSCs are restricted to stage-specific embryonic antigen (SSEA)-3, SSEA-4, TRA-1-60, TRA-1-81, L1 cell adhesion molecule (L1CAM), and epithelial cell adhesion molecule (EpCAM) (Choi et al., 2014). Unfortunately, one or two surface molecule-based cell classification is insufficient to define and eliminate undifferentiated cells.…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding work by Abdal Dayem and colleagues [3] deal with convergence of nano‐sized materials and stem cells by using unique properties of silver nanoparticle to induce neuronal differentiation of cells. Choi et al [4] identify human embryonic stem cell surface markers by monoclonal antibodies, and develop antibody approaches to prepare clinically transplantable cells. Kawahara and colleagues [5] apply the technique of single chain Fv (scFv)/receptor chimeras named “signalobodies” in a myeloid progenitor cell line, and examined the corresponding signaling pathways.…”
mentioning
confidence: 99%